Performance Analysis of a Transcritical CO2 Heat Pump with Mechanical Subcooling for Space Heating - Dai Baomin; Ju Chengcheng; Liang Mengtao; Liu Shengchun; Sun Zhili; Qi Haifeng; Ma Yitai (Zhileng xuebao)
The thermal performance of a traditional transcritical CO2 heat pump for space heating in winter can be improved by mechanical subcooling using a simple vapor-compression cycle. A thermodynamic model is developed in this study to analyze the operating characteristic of a CO2 heat pump system for space heating using mechanical subcooling. The results indicate that a maximum coefficient of performance (COP) exists at optimum discharge pressure and subcooling degree. The COP improves by 15.9% under a standard working condition compared with that in the traditional CO2 heat pump. This system can effectively solve the problem of rapid COP deterioration at a relatively high return water temperature. The COP of the CO2 heat pump that employs mechanical subcooling only decreases by 8.4% as the return water temperature increases from 40 to 50 ℃, whereas that of the traditional CO2 system decreases by as high as 16.9%. Moreover, the discharge pressure and temperature can be effectively reduced. The advantage in the pressure reduction is more pronounced at lower return water temperature. The overall energy efficiency of the heat-pump system is influenced by the selection of the working fluid used in the mechanical subcooling cycle. Ammonia (R717) achieves the highest energy efficiency among the 11 samples, and the lowest energy efficiency is realized in the use of R1234yf refrigerant. The thermal performance more significantly improves at low ambient temperature. Furthermore, the scale of the mechanical subcooling cycle that uses a traditional refrigerant is relatively small compared with that of the CO2 heat pump system. Employing the mechanical subcooling method is an economical solution to improve the overall thermal performance of a transcritical CO2 heat pump for space heating.